Contemporary Natural Philosophy and Philosophies - Part 2 - Dodig-Crnkovic, Gordana; Schroeder, Marcin J. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Modern technology has eliminated barriers posed by geographic distances between people around the globe, making the world more interdependent. However, in spite of global collaboration within research domains, fragmentation among research fields persists and even escalates. Disintegrated knowledge has become subservient to the competition in the technological and economic race, leading in the direction chosen not by reason and intellect but rather by the preferences of politics and markets. To restore the authority of knowledge in guiding humanity, we have to reconnect its scattered isolated parts and offer an evolving and diverse but shared vision of objective reality connecting the sciences and other knowledge domains and informed by and in communication with ethical and esthetic thinking and being. This collection of articles responds to the second call from the journal Philosophies to build a new, networked world of knowledge with domain specialists from different disciplines interacting and connecting with the rest of the knowledge-producing and knowledge-consuming communities in an inclusive, extended natural-philosophic, human-centric manner. In this process of reconnection, scientific and philosophical investigations enrich each other, with sciences informing philosophies about the best current knowledge of the world, both natural and human-made, while philosophies scrutinize the ontological, epistemological, and methodological foundations of sciences.